MULTISENSORY METHODS AS TEACHERS' EFFORTS IN DEALING WITH DYSLEXIC CHILDREN IN ELEMENTARY SCHOOL: LITERATURE REVIEW - Putri, Yuris Ahmadi Utomo; Hendriani, Wiwin (Psychosophia: Journal of Psychology, Religion, and Humanity, 2024)
Dyslexic children of primary school age feel unable to keep up with learning, because they have different ways to learn. Teachers in school need to strategize a method for dyslexic children can follow the lesson well. This study aims to determine the efforts of teachers in dealing the dyslexic children with multisensory methods in elementary school. The research method used is integrative literature review with a five-stage framework, namely problem identification, literature search, data evaluation, data analysis, and presentation of findings. The electronic databases used are Sinta, ResearchGate, Google Scholar, Garuda, and Rama Repository, producing amount 38,649 articles over the past 10 years. Using search keywords, 7 journals were identified as meeting the inclusion criteria using the CASP (Critical Appraisal Skill Program) instrument. The result of this literature review is that multisensory methods are proven to improve the reading ability and learning quality of dyslexic children. Children experience an improvement in their ability to recognize words accurately although not significantly. Teachers need to provide remedial to overcome the difficulties and learning barriers they experience at school, and discuss with parents in order to children get a balanced teaching method between home and school.